1990
DOI: 10.1159/000235190
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Activation in Sterile Bladder and Prostate Inflammation

Abstract: Sterile inflammation of the bladder has often been associated with interstitial cystitis (IC), a urologic condition of unknown etiology, predominantly affecting young and middle-aged females, for which no effective therapy is known. Recent reports have indicated that IC is associated with an increased number of bladder mast cells. Here we report the case of a middle-aged man with chronic sterile hematuria, dysuria and lower abdominal pain associated with a high number of bladder and prostate mast cells. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…208 Expressed prostatic secretions from men with CP/CPPS had increased mast cell tryptase and NGF levels, 211 and a later study confirmed that tryptase and carboxypeptidase A (CPA3), a marker of mast cell activation, were also increased in the urine of CP/CPPS patients. 212 The extent of mast cell degranulation or activation has varied between studies as both altered granular structure 213 and a decrease in the number of intact mast cells 214 have been observed in biopsies from CP/CPPS patients, implying that mast cell activation without complete degranulation, as well as a higher rate of complete mast cell degranulation, respectively, could occur in CP/CPPS. The potential role for mast cells in the onset and maintenance of CP/CPPS has been a major focus of animal research on this syndrome thus far.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndromementioning
confidence: 99%
“…208 Expressed prostatic secretions from men with CP/CPPS had increased mast cell tryptase and NGF levels, 211 and a later study confirmed that tryptase and carboxypeptidase A (CPA3), a marker of mast cell activation, were also increased in the urine of CP/CPPS patients. 212 The extent of mast cell degranulation or activation has varied between studies as both altered granular structure 213 and a decrease in the number of intact mast cells 214 have been observed in biopsies from CP/CPPS patients, implying that mast cell activation without complete degranulation, as well as a higher rate of complete mast cell degranulation, respectively, could occur in CP/CPPS. The potential role for mast cells in the onset and maintenance of CP/CPPS has been a major focus of animal research on this syndrome thus far.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndromementioning
confidence: 99%
“…Although little work has been conducted to determine the role of the mast cell in MCPPS IIIA, case reports such as that submitted by Theoharides et al [48] suggest that mastocytosis and elevated urinary histamine levels might be observed in some patients with prostatitis. This correlates well with an estrogen-induced model of prostatitis where increased numbers of degranulated mast cells were noted [49].…”
Section: Mast Cell Activationmentioning
confidence: 99%
“…Dye bind ing of the glycosaminoglycans is well preserved in the latter fixative [19], IFAA fixation reportedly increases the yield of stainable mast cells by approximately 25% in human bladder tissue [19,20). Samples (5-um thick) were stained with 0.25% toluidinc blue, pH 2.5, for 45 min to allow the identification of aldehyde-susceptible mast cells which differentiate mucosal mast cells (MMC, staining blue) from connective tissue mast cells (CTMC, staining metachromatically vio let).…”
Section: Fixation and Staining For Light Microscopymentioning
confidence: 99%
“…Thin sections (50-70 nnt) were cut on an LKB 8801 ultramicrotome and stained with uranyl acetate and lead citrate (Fisher Scientific, Pittsburgh. Pa., USA): they were then examined with a JEOL-100 electron microscope [20,21 ].…”
Section: Fixation and Preparation For Electron Microscopymentioning
confidence: 99%